Study of the Influence of Pyrolysis Conditions on the Textural Properties of Physically Activated Biochars - Di Stasi, Christian; Greco, Gianluca; Videgain, María; González, Belén; Manyà, Joan J. (Jornada de Jóvenes Investigadores del I3A, 2019)
Nine wheat straw-derived biochars were produced under different pyrolysis conditions (i.e. peak temperature, absolute pressure, and pyrolysis atmosphere) and subsequentially activated with CO2 at 800 °C in order to study the influence of the pyrolysis operating conditions on the textural properties of the resulting activated biochars.